Genetic Variability among growth and seed yield attributes of Jatropha curcas (L.) - Kumar, Sudhir; Pandey, S.K.; Ranjan, Rajeev; Dhyani, S.K.; Kumar, R.V.; Ahlawat, S.P. (Indian Journal of Agroforestry, 2020)
Twelve accessions of Jatropha curcas collected from three states were grown in randomized block design and evaluated for growth and yield characters. Findings revealed significant differences (p>0.5% and 0.1% level) among all the accessions for their growth parameters. Significant positive correlations (r =0.388 to 0.955, p